Biological evaluation of a novel bilirubin adsorbent and its therapeutic effect on animal models of hyperbilirubinemia. Issue 4 (12th November 2021) - Su, Rui; Chen, Guanming; Yan, Lihua; Liu, Wei; Zhao, Shengjiang; Dai, Qinghai; Yuan, Shi; Shen, Xiaomin; Yu, Wanyou; Gong, Xiaojie; Yu, Meili
Abstract: Hyperbilirubinemia caused severe hepatobiliary diseases with various causes, especially hepatic fibrosis and cirrhosis caused by end‐stage hepatitis B and C. Plasma adsorption perfusion (PP) has a tremendous advantage in treating patients with hyperbilirubinemia and liver failure, wherein, a safe and effective adsorbent is the key to filter out bilirubin successfully in PP. In this work, a simple engineering strategy, a new porous polymer adsorption resin ERM‐0100 based on the homopolymer predispersion system, is proposed to produce high‐performance bilirubin adsorbents. Preliminary experimental results show that ERM‐0100 exhibits a large surface area and uniformly porous structure. Experimental results verify that ERM‐0100 has high biocompatibility and bilirubin adsorption efficiency (TBIL:35%, direct bilirubin [DBIL]:30%, IBIL:87%) that is significantly higher than most of the reported adsorbents. Animal experiments prove that ERM‐0100 has high bilirubin adsorption efficiency and can improve the liver function of animals. The combination of high biocompatibility and high adsorption capacity positions the ERM‐0100 as a promising candidate for bilirubin removal.